Pengaruh Literasi Keuangan, Efikasi Keuangan dan Faktor Demografi Terhadap Pengambilan Keputusan Investasi Pada Investor Galeri Investasi Universitas Muhammadiyah Kupang - Hervina Hilda Dinung; Abdul Malik Hasyim; Fitriningsih Amolo (Jurnal Manajemen, 2022)
The purpose of this study is (1) to find out and analyze whether financial literacy has a significant effect on investment decision making at the Investment Gallery Investors of the University of Muhammadiyah Kupang, (2) to determine and analyze whether financial efficacy has a significant effect on investment decision making at the University Investment Gallery Investors. Muhammadiyah Kupang, (3) to find out and analyze whether demographic factors have a significant effect on investment decision making at the Investment Gallery Investors, Muhammadiyah Kupang University, (4) to determine and analyze whether financial literacy, financial efficacy, and demographic factors simultaneously influence decision making. investment in Investors Investment Gallery, University of Muhammadiyah Kupang. The type of data used in this study is primary data, namely data obtained through the distribution of questionnaires distributed to respondents, totaling 79 samples, and the total population being 79 people. The data analysis method used to answer the research objectives is instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing is done by fulfilling partial test, simultaneous test (f) with significant level (a) 5%, and coefficient test. determination (R2). The result data in this study used the SSPS 16.0 program. The results showed (1) partially financial literacy had an effect on investment decision making at Investment Gallery Investors, Muhammadiyah University of Kupang with a value of Tcount 2.422> Ttable 1.664 and a significant value of 0.018 <0.05. (2) Simultaneously, financial efficacy affects investment decision making at the Investment Gallery Investor, Muhammadiyah University of Kupang with a value of Tcount 3.658> Ttable 1.664 and a significant value of 0.000 <0.05. (3) Simultaneously, demographic factors affect investment decision making at the Investment Gallery Investor, Muhammadiyah University of Kupang with a value of Tcount 3,012> Ttable 1,664 and a significant value of 0.004 <0.05.